Level of Capabilities of Public School Managers in Isabela to Respond to Disaster Risk Management Programs - Pattalitan, Lucila (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study assessed the status of implementation and level of capabilities of the Disaster Risk Reduction and Management (DRRM) Program in the public schools of Isabela. Anchored on the four-phase disaster management model covering mitigation, preparedness, response, and recovery, the study used a descriptive-correlational research design. Data were gathered through a structured questionnaire administered to 137 school heads and 480 teachers from elementary and secondary public schools in Alicia, Angadanan, Cabatuan, Ramon, and San Mateo. The instrument measured respondent profile, DRRM implementation, and DRRM capabilities, and was validated by experts with an S-CVI of 1.00 and reliability coefficients of 0.94 and 0.91. Findings showed that DRRM implementation was rated high in disaster prevention and mitigation, preparedness, response, and rehabilitation and recovery. The schools’ capabilities were also rated high in human resources, material facilities, knowledge, innovation and education, policies, plans and procedures, and capacities and mechanisms. However, limited DRRM training participation among school personnel remained a key concern. The results further revealed significant but very weak to weak relationships between respondent profile and DRRM implementation and capabilities, while implementation status and capability level showed significant moderate to strong associations. The study recommends stronger school-LDRRMC collaboration, mandatory DRRM training, improved financial and logistical support, enhanced curriculum integration, and community-based preparedness activities. The study supports SDG 4, SDG 11, SDG 13, SDG 16, and SDG 17 by promoting safe schools, resilient communities, climate preparedness, effective governance, and institutional partnerships. Its sustainability impact lies in strengthening educational, community, institutional, and disaster governance systems for safer and more resilient public schools.
Keywords: Capacities and Mechanisms; Disaster Preparedness; Disaster Prevention and Mitigation; Disaster Response; Disaster Risk Reduction and Management; DRRM Capabilities; Public Schools; Teachers; School Heads